2014
DOI: 10.3892/ol.2014.2108
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alterations of chromosomes, p53 and p16 genes in low- and high-grade bladder cancer

Abstract: A majority of patients with bladder cancer present with superficial disease and subsequently, some patients show progression to muscle invasive or metastatic disease. Bladder cancer has a complex genetic process and identification of the genetic alterations which occur during progression may lead to the understanding of the nature of the disease and provide the possibility of early treatment. The aim of the present study was to compare the structural and numerical chromosomal differences and changes in the p16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…[67] Studies on urothelial bladder carcinoma cell lines showed that these two signaling pathways had different degrees of changes including p53 mutation, pl4 homozygous deletion, RB gene hypermethylation or pl6 homozygous deletion. [68][69][70] Studies on other 12 invasive urothelial bladder carcinoma tumor tissues showed the same results of two signaling pathway changes. [11,71] Mutated p53 protein could not exert cell cycle regulatory function.…”
Section: Retinal Blastomasupporting
confidence: 62%
“…[67] Studies on urothelial bladder carcinoma cell lines showed that these two signaling pathways had different degrees of changes including p53 mutation, pl4 homozygous deletion, RB gene hypermethylation or pl6 homozygous deletion. [68][69][70] Studies on other 12 invasive urothelial bladder carcinoma tumor tissues showed the same results of two signaling pathway changes. [11,71] Mutated p53 protein could not exert cell cycle regulatory function.…”
Section: Retinal Blastomasupporting
confidence: 62%
“…Alteration of the p16 and p15 genes which occurs at 9p21 appears to be a common event in bladder cancer and p16 has been proposed to be the major deletion target. The frequent inactivation of p16 has been shown to be associated with the progression of bladder cancer to a more malignant phenotype [3032]. Meanwhile, transduction of p16 antitumor peptide displayed inhibition of bladder cancer in mouse model, which indicated the restoration of p16 to be a probable treatment of bladder cancer [33].…”
Section: Discussionmentioning
confidence: 99%
“…The gene encoding p16 is mutated or downregulated in several cancer cells. Breast carcinoma progression has been related to overexpression of p16 [14], and this has been reported in head and neck squamous carcinoma [15], in prostate carcinoma [16], and also in aggressive subtypes of bladder carcinoma [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%